Performance analysis on round trip available bandwidth estimation tools for wireless mesh network - Imran Edzereiq, Kamarudin; M. A., Ameedeen; Z. R. M., Azmi; M. I. U., Ong; Abbas Saliimi, Lokman (Universiti Malaysia Pahang, 2019)
In wireless mesh network environment, available bandwidth (ABW) estimation is important to provide feedback on the quality of network infrastructure to end user. Recent study shows the emerging of Round Trip (RT) based ABW tools where it eliminates the need of having a receiver end. However, these tools are not fully tested in various network environment and benchmark with existing widely used ABW tools. In this paper, we perform an extensive experimental analysis study on RT based tools with other widely used ABW tools by looking at the accuracy and consistency. In term of accuracy and consistency, RT based tools excel in these conditions.